Pinjaman Online dan Krisis Tanggung Jawab Keluarga Kristen - Valentino, Peter Owen; Sirait, Hikman; Selviawati, Selviawati (Peneliti.net, 2025)
The development of digital technology and the advancement of culture have consciously changed the economic landscape and lifestyle, including that of Christian families. The availability of easily accessible online loan services, in line with a consumerist culture reinforced by social media and digital branding narratives, has led many families to fall into debt without careful consideration. This has led to a crisis of responsibility in household financial management, impacting spiritual life and the witness of faith. Phenomena emerging in the field reveal economic pressure within families, relational conflicts, and social sanctions resulting from the burden of online loan debt. The purpose of this study is to examine the theological and ethical aspects of digital debt culture and its implications for the responsibility of Christian families. Using a qualitative method with a theological literature review approach and phenomenological analysis, it can be concluded that Christianity can understand the nature of online loans and debt culture within a theological ethical framework. This can build the moral responsibility of Christian families against the threat of consumerism. Thus, Christian ethics regarding debt culture can be actualised in the church through church financial ethics education, as the crisis of responsibility within Christian families stems from the lack of faith-based financial ethics education. Additionally, the absence of pastoral guidance on managing blessings and living simply exacerbates the issue.